Determinats Disclousure Sustainability Development Goals (SDGs) In Asean Countries - Setyawan, Wahyu; Saputra, Muhammad Riyadhi (Economics and Business Solutions Journal, 2025)
This study aims to analyze the impact of the implementation of the Global Reporting Initiative (GRI) and the Sustainability Accounting Standards Board (SASB) on the quality of Sustainable Development Goals (SDGs) disclosure in six ASEAN countries: Indonesia, Malaysia, Thailand, Singapore, Vietnam, and the Philippines. A quantitative approach was employed, utilizing secondary data from sustainability reports for 2022-2023, analyzed using panel data regression with a fixed effects model. The results indicate that both independent variables have a significant positive partial effect on SDGs disclosure. The SASB variable demonstrated a significant influence with an error rate of 14%, while the GRI variable was significant with a 3.7% error rate. These findings indicate that the adoption of specific sustainability reporting standards SASB with its focus on industry-specific material topics and GRI with its comprehensive framework effectively enhances corporate transparency and accountability in achieving sustainable development objectives. This research provides practical implications for policymakers and regulators in the ASEAN region to promote the harmonization and adoption of standardized reporting frameworks to improve the quality of SDGs disclosure, which can ultimately attract investment, create jobs, and improve societal welfare. The originality of the study lies in its application of the Sustainability Maturity Model theoretical framework and the use of panel data regression analysis to investigate the complex interactions between these variables within the ASEAN context.